An Accurate Cartesian Method for Incompressible Flows with Moving Boundaries (Communications in Computational Physics, 2014)
An accurate cartesian method is devised to simulate incompressible viscousflows past an arbitrary moving body. The Navier-Stokes equations are spatially discretized onto a fixed Cartesian mesh. The body is taken into account via the ghost-cellmethod and the so-called penalty method, resulting in second-order accuracy in velocity. The accuracy and the efficiency of the solver are tested through two-dimensionalreference simulations. To show the versatility of this scheme we simulate a three-dimensional self propelled jellyfish prototype.